Contraceptive Knowledge, Attitude and Behavior of Contraception in Teenage Pregnancy at Buddhachinaraj Phitsanulok Hospital - Monwanee Muangchang; Pallop Pongsuthirak (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives: To assess characteristics, knowledge, attitude and behavior in contraception among pregnant teenagers. Materials and Methods: The cross-sectional descriptive study was conducted from September 2015 to February 2016 in pregnant teenagers (under 20-year-old) attending ANC or admitted at Buddhachinaraj Phitsanulok Hospital. The questionnaires consisted of general characteristics, contraceptive behavior, contraceptive knowledge, and contraceptive attitude. The data was analyzed using descriptive statistics, Chi square test and Spearman's rank-order correlation.results: Three hundred and fifty pregnant teenagers were divided into two groups by using contraceptive knowledge mean scores (14.68). The above mean group (group A) composed of 192 teenagers (54.86%) and the below mean group (group B) had 158 teenagers (45.14%). There were significant differences in educational level (p = 0.033), gravidity (p = 0.006) and contraceptive attitude (p < 0.05) between groups. The two most common contraceptive methods were oral contraceptive pills (OCP) (66.86%) and condoms (30.29%) but the future choices will be depot medroxyprogesterone acetate (DMPA) (51.71%) and OCP (28.57%). The main sources of contraceptive knowledge were internet and school. If they had any problems, they asked their friends (47.14%) and used the internet (45.14%).Conclusion: About a half of pregnant teenagers had contraceptive knowledge scores above mean. There was a significant difference in level of education, gravidity, and attitude between the two groups. The most common contraceptive method previously used was OCP but future contraceptive choice will be DMPA.